Hashemite Kingdom of Jordan - Development Policy Review : Improving Institutions, Fiscal Policies and Structural Reforms for Greater Growth Resilience and Sustained Job Creation (Vol. 1 of 2) - World Bank (Washington, DC, 2013)
Jordan's quest for long-term, inclusive and sustainable growth has remained largely elusive. By the Growth and Development Commission's measure of success, namely, an average growth rate of 7 percent over 30 years, Jordan's growth record cannot be dubbed 'successful'. This Development Policy Review (DPR) shows that sustaining growth and reducing unemployment is possible: Jordan has a strong human capital base, a large endowment in engineers, doctors, accountants, Information Technology (IT) specialists and a substantial highly-skilled diaspora (500,000 educated Jordanians abroad, 8 percent of the population). Furthermore, the market-oriented reforms of the early 2000s have made Jordan one of the most open economies in the Middle East and North Africa Region and have led to the emergence of dynamic non-traditional sectors (e.g., information and communication technologies, health tourism and business services). What is missing are: (i) an adequate and stable institutional framework for policymaking and long-term business development; (ii) good fiscal policies to manage shocks and maintain macroeconomic stability; good institutions and macroeconomic stability were identified by the growth commission as two of the five common characteristics of successful growth experiences; and (iii) further growth-enhancing structural reforms.